Municipal solid waste gasification for resilient energy systems: advancing sustainable crisis preparedness in the wake of COVID-19 - Rehan, Mohammad; Shahzad, Khurram; Ali, Nadeem; Nizami, Abdul-Sattar (Frontiers in Bioengineering and Biotechnology, 2025)
The pandemic increased global waste problems, especially medical and MSW (Municipal Solid Waste), showing the urgent need for sustainability. This research evaluates the environmental and economic sustainability of transforming MSW into syngas and electricity via gasification, using life cycle assessment (LCA) and techno-economic analysis. This research simulates syngas production and energy recovery for a 50-ton-per-day gasification plant, with a focus on waste disposal in Jeddah, Saudi Arabia. The LCA findings reveal substantial overall reductions in environmental impacts, with a climate change benefit of −100 kg CO2 eq. per ton of waste processed, alongside offsets in fossil depletion (−32.5 kg oil eq.) and particulate matter formation (−0.025 kg PM2.5 eq.). Financially, the system is sound, generating $516,474 yearly, with a 4.8-year return and 208% return on investment (ROI). The research supports various Sustainable Development Goals (SDGs), including SDG 7, SDG 12, and SDG 13, while also addressing waste issues related to the COVID-19 pandemic. Pilot-scale validation is necessary to address real-world variability when relying on simulated data. The results support gasification as a robust, circular technology for enhancing general MSW management resilience, providing policymakers with a path for transitioning MSW waste to energy in cities and during emergencies.